Analysis of the course of chronic pancreatitis: pancreatic burnout rates are only increased in a subgroup of patients with alcoholic chronic pancreatitis - Hirth, Michael; Härtel, Nicolai; Weiß, Christel; Ebert, Matthias; Schneider, Alexander (Pancreas, 2019)
ObjectivesThe pancreatic burnout hypothesis postulated an increasing absence of pain with simultaneous functional insufficiency in advanced stages of chronic pancreatitis (CP). However, the underlying data remain scarce and contradictory. We aimed to analyze, first, the frequency of a pancreatic bur